Microbiota-derived short-chain fatty acids mediate the effects of dengzhan shengmai in ameliorating cerebral ischemia via the gut–brain axis. (24th April 2023) - Guo, Hui-Hui; Shen, Hao-Ran; Tang, Ming-Ze; Sheng, Ning; Ding, Xiao; Lin, Yuan; Zhang, Jin-Lan; Jiang, Jian-Dong; Gao, Tian-Le; Wang, Lu-Lu; Han, Yan-Xing
Abstract: Ethnopharmacological relevance: Dengzhan shengmai (DZSM) formula, composed of four herbal medicines ( Erigeron breviscapus, Panax ginseng, Schisandra chinensis, and Ophiopogon japonicus ), is widely used in the recovery period of ischemic cerebrovascular diseases; however, the associated molecular mechanism remains unclear. Aim of the study: The purpose of this study was to uncover the links between the microbiota–gut–brain axis and the efficacy of DZSM in ameliorating cerebral ischemic diseases. Materials and methods: The effects of DZSM on the gut microbiota community and bacteria-derived short-chain fatty acid (SCFA) production were evaluated in vivo using a rat model of cerebral ischemia and in vitro through the anaerobic incubation with fresh feces derived from model animals. Subsequently, the mechanism underlying the role of SCFAs in the DZSM-mediated treatment of cerebral ischemia was explored. Results: We found that DZSM treatment significantly altered the composition of the gut microbiota and markedly enhanced SCFA production. The consequent increase in SCFA levels led to the upregulation of the expression of monocarboxylate transporters and facilitated the transportation of intestinal SCFAs into the brain, thereby inhibiting the apoptosis of neurocytes via the regulation of the PI3K/AKT/caspase-3 pathway. The increased intestinal SCFA levels also contributed to the repair of the 2VO-induced disruption of gut barrier integrity and inhibited the translocation of lipopolysaccharide from the intestine to the brain, thus attenuating neuroinflammation. Consequently, cerebral neuropathy and oxidative stress were significantly improved in 2VO model rats, leading to the amelioration of cerebral ischemia-induced cognitive dysfunction. Finally, fecal microbiota transplantation could reproduce the beneficial effects of DZSM on SCFA production and cerebral ischemia. Conclusions: Our findings suggested that SCFAs mediate the effects of DZSM in ameliorating cerebral ischemia via the gut microbiota–gut–brain axis. Graphical abstract: Image 1 Highlights: Dengzhan Shengmai (DZSM) significantly altered the composition of the gut microbiota and greatly enhanced SCFA production and transport. DZSM improved cognition-related dysfunction in 2VO model rats via SCFAs. SCFAs mediated the inhibitory effect of DZSM on the apoptosis of cerebral neurocytes. DZSM reduced neuroinflammation via the SCFA–gut barrier–brain axis.